2014
DOI: 10.1111/and.12257
|View full text |Cite
|
Sign up to set email alerts
|

Relation between male obesity and male infertility in a Tunisian population

Abstract: Obesity is associated with significant disturbance in the hormonal milieu that can affect the reproductive system. Male infertility affects approximately 6% of reproductive-aged men. It has been suggested that overweight men or men with obese body mass index (BMI) experience prolonged time to pregnancy, although the influence of male BMI on fertility remains understudied. We hypothesised that BMI is inversely correlated with fertility, manifested by reduced sperm concentration and varicocele. Males of mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…There are also studies reporting the negative effect of obesity on motility and ejaculate volume [ 16 , 17 ]. In a study similar to ours, where the infertility-associated risk factors were excluded, the sperm concentration was found to be negatively correlated with increased BMI [ 10 , 18 ] but we did not detect any such correlation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies reporting the negative effect of obesity on motility and ejaculate volume [ 16 , 17 ]. In a study similar to ours, where the infertility-associated risk factors were excluded, the sperm concentration was found to be negatively correlated with increased BMI [ 10 , 18 ] but we did not detect any such correlation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Research articles on humans published in English from 1965 to 2015 were included in this report [23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). .…”
Section: Data Extraction and Data Anaysismentioning
confidence: 99%
“…The result from several studies suggested that obesity was an important risk factor for non-alcoholic fatty liver disease [4], hypertension [5], inflammation [6] and cancer [7]. Interestingly, data suggested obesity has a negative impact on male reproductive system and fertility over the past decade [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%